A comparative study of supine lying, side lying and prone positioning on oxygen saturation, in mechanically ventilated patients, in acute respiratory failure - Patil, Prajakta S.; Nagarwala, Raziya (International Journal of Research in Medical Sciences, 2017)
Background: Body positioning refers to optimize O2 transport by manipulating effect of gravity on cardiopulmonary and cardiovascular function. Positioning should be an integral part of respiratory care, especially when prophylaxis is aim. Turning patient supine to lateral to prone to lateral, at least hourly makes a difference between living and dying for intensive care patient. Positioning reduces atelectasis and improves gas exchange. Methods: Total 33 subjects aged between 15-73 years, 21 male and 12 female patients were selected for study from ICU, Neurological trauma unit Pune. Inclusion criteria: All subjects with respiratory failure due to different pathologies like ARDS, Pulmonary edema, pneumonia, tuberculosis, collection of fluid in pleural cavity with underlying lung collapse. Exclusion criteria: Unstable cardiac conditions, unstable fractures, unstable hemodynamic, recently operated cardiac subjects. The patients were kept in supine position, lateral and prone and vitals like BP, HR, RR and oxygen saturation with help of pulse oximeter noted just before position. Thorough ET or tracheostomy suction was done. Before turning patient if any intercostal drain present was clamped. Results: Paired t-test was used. p values for prone and bilateral side lying positions was < 0.05 showing its significance for above mentioned 3-positions. p value for supine was not < 0.05 showing its non-significance. Conclusion: The study concluded that oxygen saturation improves in prone lying and side lying position as compared to supine lying. But this improvement is quiet significant in prone position as compared to side lying.